A torque matched aerodynamic performance analysis method for the horizontal axis wind turbines - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Weber, Horst; Delgado, Antonio (Wind Energy, 2013)
An analysis method is developed to test the operational performance of a horizontal axis wind turbines. The rotor is constrained to the torque-speed characteristic of the coupled generator. Therefore, the operational conditions are realized by matching the torque generated by the turbine over a selected range of incoming wind velocity to that needed to rotate the generator. The backbone of the analysis method is a combination of Schmitz' and blade element momentum (BEM) theories. The torque matching is achieved by gradient-based optimization method, which finds correct wind speed at a given rotational speed of the rotor. The combination of Schmitz and BEM serves to exclude the BEM iterations for the calculation of interference factors. Instead, the relative angle is found iteratively along the span. The profile and tip losses, which are empirical, are included in the analysis. Hence, the torque at a given wind speed and rotational speed can be calculated by integrating semi-analytical equations along the blade span. The torque calculation method is computationally cheap and therefore allows many iterations needed during torque matching. The developed analysis method is verified experimentally by testing the output power and rotational speed of an existing wind turbine model in the wind tunnel. The generator's torque rotational speed characteristic is found by a separate experimental set-up. Comparison of experiments with the results of the analysis method shows a good agreement.
UnivIS-Import:2015-03-09:Pub.2014.tech.ITC.stmmec.atorqu
Keywords: BEM theory; Horizontal axis wind turbine; Optimization; Power coefficient and performance measurements; Schmitz' theory